Hjälpmedels betydelse som arbetsterapeutisk intervention för personer med demenssjukdom : En litteraturstudie - Eriksson, Agnes; Holmberg, Carina (2015)
The aim of this literature review was to describe the meaning of assistive devices as occupational therapy intervention for people with dementia. The data was carried out through a literature search in the databases available at Luleå University of Technology, one article was also added from a secondary search. The quality of the articles were examined to determine whether they were suitable for inclusion in the study. The result was based on eleven articles, including nine qualitative and two quantitative. Articles were analyzed by developing similarities and differences. The results are reported in three categories; Assistive devices support independence and participation, Assistive devices reduces anxiety and stress for caregivers and family members and The function and design of assistive devices affect use. The result showed the importance of assistive device in that they perceived to be time-saving, had the potential to reduce stress, contributed to reduced anxiety and increased safety. It also revealed aspects of irritation, frustration and anxiety associated with the use of assistive devices. The result showed that people with dementia are in need of support from others to use assistive devices at a later stage of the disease. In some cases the persons with dementia can not use the assistive device in an independent way without support. The conclusion is that the meaning of assistive devices contributes to both positive and negative aspects. Validerat; 20150607 (global_studentproject_submitter)